The Perceptions of Instructors and Students on Native Speakerism in Terms of English Language Teaching, English Variations, and Culture - Cengiz, Seçil; Mede, Enisa (English Language in Focus (ELIF), 2024)
This study aimed to explore the views of both preparatory school instructors and students concerning native speakerism within the context of English Language Teaching (ELT), English language variations, and culture. The research involved 171 preparatory students and 70 instructors affiliated with a non-profit university in Istanbul, Turkey. Employing a mixed methods approach, this study sought to comprehend the perspectives of these participants. Quantitative data were gathered through surveys adapted from Liu (2018), while qualitative insights were obtained via semi-structured interviews with instructors. The collected data underwent analysis using SPSS and content analysis techniques. The analysis of student perceptions, categorized by gender and proficiency levels, revealed no significant disparities in their views on ELT and culture. Nonetheless, differences surfaced among A1 and A2 level students concerning English variations. In contrast, instructors' perceptions, factoring in their years of experience and academic qualifications, exhibited no variations in relation to ELT, English variations, and culture. Qualitative findings indicated that instructors had positive attitudes toward teaching diverse cultures and English language varieties. Moreover, instructors expressed the belief that discrimination between native and non-native instructors should cease.